Sistem Informasi Administrasi Pasien Rawat Jalan dan Rawat Inap Berbasis Web - Nasrullah; Ihsanuddin; Imilda (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2024)
Hospitals, as public service institutions, require an accurate, reliable, and adequate information system to enhance their services to patients and related environments. Given the extensive scope of services, many complex issues arise in the hospital's service processes. The numerous variables involved in hospital operations influence the speed of information flow required by both users and the hospital environment. Manual data management in hospitals presents significant drawbacks, including slow processing time and a high risk of errors. With the support of current information technology, manual data management can be replaced by a computerized information system. In addition to being faster and easier, data management becomes more accurate. Accurate data processing results in accurate information, which is crucial for decision-making, both for management and others. The purpose of this study is to facilitate patient registration for outpatient and inpatient visits, ease report generation, and assist the hospital management in improving service quality and decision-making processes. Based on the research conducted at Zainoel Abidin General Hospital in Aceh, the implementation of the outpatient and inpatient patient administration information system has proven to be precise and accurate, particularly in the pharmacy department. The system has also made it easier to obtain patient information and has addressed frequent issues such as challenges in monitoring and supervising patients and medical records. The system development lifecycle (SDLC) was utilized in designing this system.